Effect of Incorporation of Liver Protein Hydrolysate on Processing Characteristics of Fibre-Enriched Meat Loaves : doi: 10.5958/2581-6616.2021.00011.6 - Verma, Akhilesh K.; Chatli, Manish Kumar; Kumar, Pavan; Mehta, Nitin (Journal of Meat Science, 2022)
Present study was conducted for evaluation of effect of addition of porcine liver protein hydrolysates into formulation of pork loaves at four different levels viz. Control (0% C), 0.09% LA (T1), 0.06% LT (T2) and 0.09% LP (T3) and compared for different physico-chemical, instrumental texture and colour profile, and sensory quality attributes. Emulsion stability, pH and cooking yield value varied significantly among hydrolysate added sample than control whereas, fat content remained comparable amongst all groups. Products pH, moisture, ash, carbohydrate, energy content, cooking yield, cooking loss, and moisture retention of pork loves varied significantly (P<0.05) than control. However, water activity, protein, fat, fibre, fat retention and moisture protein ratio did not differ significantly (P>0.05) for both test and control. Liver hydrolysate addition in pork loaves resulted in significant reduction in lightness (L*), yellowness (b*) and chroma value whereas redness (a*) and hue value remained comparable among all groups. All attributes of textural profiles varied significantly (P<0.05) with incorporation of liver hydrolysate as compared to control except cohesiveness. All sensory attributes were rated higher for pork loaves with 0.06% porcine liver protein hydrolysate. Therefore, result concluded that pork loaves with 0.06% liver hydrolysate was most suitable for preparation of meat loaves.